Analisis Penggunaan Educaplay sebagai Digital Assessment Tools dalam Pembelajaran Pendidikan Agama Islam di SMA Sabilurrosyad Malang - Fina Hushunul Ahadiyah; Biaunika Ana Fika; Luthfiya Fathi Pusposari; Indah Aminatuz Zuhriyah (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This research is driven by the rapid development of digital technology that encourages innovation in learning and assessment processes, particularly through the use of digital assessment tools. The aim of this research is to analyze how Educaplay serves as a digital evaluation tool in Islamic Education (PAI) learning at SMA Sabilurrosyad Malang. This research employed a quantitative approach with a descriptive quantitative design. The subjects of this study were 20 of tenth-grade students selected through purposive sampling. Data were collected using a Likert-scale questionnaire and analyzed using descriptive statistical techniques. The results show that the use of Educaplay, particularly the Froggy Jumps feature, facilitates the assessment process, enhances students’ activeness, motivation, and understanding. Educaplay provides convenience for teachers in evaluating student performance through automatic scoring systems. However, several challenges were identified, including unstable internet connections, limited access to facilities, and varying levels of students’ digital literacy. Therefore, the use of Educaplay as a digital assessment tool in PAI learning is effective but requires adequate infrastructure and digital readiness.